PERTALIAN TRADISI KERIS TANGGUH NGÉNTHA-ÉNTA YOGYAKARTA: Titik Awal dan Kebangkitan Historis - Supriaswoto Supriaswoto; Timbul Haryono (Institut Seni Indonesia Yogyakarta, 2012)
Kerris is stabbing weapon for the archipelago wich have a term of religious, values, magical,aesthetic, and mysterious, but also have a politic value, economy, sociology, and art that not timeless.It prove that kerris existence still exists and continuous to exists. The one that get tracked is TangguhNgentha-entha Kerris of Yagyakarta. Who masters that become the supportersand how TangguhNgentha-entha Kerris rise back and found their identifycan be listened to in the following text. Keyword : Kerris, Tangguh Ngentha-entha, empu, Entha Wayang.